Pemberdayaan Rumah Tangga Melalui Pelatihan Usaha Rumahan Inovatif dan Digital Marketing sebagai Upaya Peningkatan Pendapatan Berkelanjutan di Kelurahan Sekip Kota Pekanbaru - Mariaty Ibrahim; Mashur Fadli; Jeneva Augustin; Etika Etika (Abdimas Indonesian Journal, 2026)
Household empowerment is a crucial strategy for enhancing community well-being and reducing families' economic dependency. While the Sekip Urban Village in Pekanbaru City possesses significant human resource potential, many households still face limitations in developing productive enterprises and leveraging digital technology for marketing purposes. The methods employed included awareness-raising sessions, training workshops, hands-on practice, and ongoing guidance to assist participants in developing home-based business products and utilizing digital media for promotion and sales. The results indicate that participants improved their knowledge and skills in managing home-based businesses, creating products with higher added value, and utilizing digital platforms to expand market reach. Furthermore, participants demonstrated increased entrepreneurial motivation and a readiness to develop their businesses independently. Consequently, training in innovative home-based business practices and digital marketing serves as an effective approach to empowering households and supporting sustainable family income growth in the Sekip Urban Village, Pekanbaru City.